2014
DOI: 10.11604/pamj.2014.17.281.165
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis in Morocco: retrospective study of 30 cases

Abstract: Cerebral venous thrombosis (CVT) is a rare origin of stroke, the clinical presentation and etiologies vary. The prognosis is shown to be better than arterial thrombosis. Magnetic Resonance Imaging (MRI) and MR Venograpgy (MRV) are currently important tools for the diagnosis. We studied 30 cases of CVT diagnosed in the department of neurology at the University Hospital of Fez (Morocco). Patients diagnosed with CVT signs between January 2003 and October 2007 were included in the study. Cerebral CT-scan was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Pregnancy and postpartum period are important risk for CVT. High predominance of female involvement was noticed with sex ratio of 2.3 in Morocco [11]. Pregnancy itself is a thrombophilic state due to the changes in blood like increased factor VIII, fibrinogen, decreased Protein S, decreased fibrinolysis, hyperemesis gravidarum, obesity, caesarean section, immobilization and other mechanical and haemodynamic factors due to pregnant state [12].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and postpartum period are important risk for CVT. High predominance of female involvement was noticed with sex ratio of 2.3 in Morocco [11]. Pregnancy itself is a thrombophilic state due to the changes in blood like increased factor VIII, fibrinogen, decreased Protein S, decreased fibrinolysis, hyperemesis gravidarum, obesity, caesarean section, immobilization and other mechanical and haemodynamic factors due to pregnant state [12].…”
Section: Discussionmentioning
confidence: 99%
“…5,50,65,73,81,93,[143][144][145][146][147][148][149][150][151][152][153][154][155][156] Considering studies distinguishing CVT occurrence pre or postpartum, we found reports of 65 cases during pregnancy and 199 cases associated with puerperium (ratio 1:3). A summary of the number of CVT cases associated with pregnancy/puerperium, the male:female ratio and the proportion of women with CVT associated with pregnancy in each cohort is described in Table 4.…”
Section: (Recommendations)mentioning
confidence: 99%
“…However, only a few studies clearly stated that women with pregnancy-related CVT received anticoagulation 73,100 and obstetric complications were not a pre-specified outcome in most studies. 81,93,137,144,145,[148][149][150]153,154,156 The anticoagulation trial by Misra et al 73 also included 12 patients with CVT related to pregnancy and, although two patients receiving UFH had vaginal bleeding, there was no reference to specific obstetric complications in pregnant or puerperal women.…”
mentioning
confidence: 99%
“…The incidence of the cerebral venous sinus thrombosis was among younger age group between 21-40 years which is in concordance with the study done by Mangshetty B et al and Vishwanath K et al 7,8 The mean age of the females in our study was 27 years which is almost similar to the study findings of Souirti Z et al, Simone et al and Basavaraj et al The study findings of Sidhom Y and Yii YL were much higher when compared to our study results. 7,[9][10][11][12] Seizure was common clinical presentation in our study and was higher in our study compared to results of Souirti Z et al, Nagarajan E et al, and Patil VC et al 9,13,14 Headache was seen in 47% of the female patients in our study and was less common presentation compared to the study findings of Souirti Z et al, Appenzeller S et al and Rajoor UG et al The other clinical presentation like seizure, pallor and anemia seen in our study was also seen in other studies. 7,9,10,11,15 The few of the risk factors like hypertension, DM seen in our study was like other studies but the incidence of the risk factors in other studies and our study varied due to difference in study population and regional differences.…”
Section: Discussionmentioning
confidence: 99%